Les enjeux de la traduction dans la réception de Haendel en Grande-Bretagne entre 1945 et 1970 - Pierre Degott (Revue LISA)
With the post-war revival of ancient music, the 1950s and 1960s were also the period when the British public rediscovered many of the Handel operas first performed between 1711 and 1741. The foundation of the Handel Opera Society (1955) by the conductor Charles Farncombe and the musicologist Edward Dent, soon followed by the creation Alan Kitching’s Unicorn Opera Group at Abingdon, gave birth to more than 40 productions of Handel operas, more often than not performed in the English language. The aim of this paper is to demonstrate to what extent the aesthetic choices of the various translators – Kitching, Dent, and a few others – were meant to acclimatize on British soil a type of repertoire completely alien to the targeted audience even though the works in question had all been composed for a London audience. After focusing on the circumstances of the Handel revival in the 1950s and 1960s, the article will show to what extent the English translations of the period considerably depart from their German contemporaries and predecessors. Pride of pride will be given to Dent’s stimulating and rather “risqué” translation of Deidamia.